2009
DOI: 10.1007/s00125-009-1319-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of metabolic enzymes in pancreatic islets of patients with type 2 diabetes

Abstract: Aims/hypothesis Glucose-stimulated insulin secretion is defective in patients with type 2 diabetes. We sought to acquire new information about enzymes of glucose metabolism, with an emphasis on mitochondrial enzymes, by comparing pancreatic islets of type 2 diabetes patients with those of non-diabetic controls. Methods Expression of genes encoding 13 metabolic enzymes was estimated with microarrays and activities of up to nine metabolic enzymes were measured. Results The activities of the mitochondrial enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 10 publications
8
87
0
3
Order By: Relevance
“…After a 4-week high fat diet, islet ACLY protein levels were significantly reduced (Fig. 2), to a similar degree as we observed in vitro and as has been reported for type 2 diabetic human islets (15). Together, these data validate our in vitro culture system and demonstrate the physiological relevance of our observations.…”
Section: Expression Of Acly In Beta Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…After a 4-week high fat diet, islet ACLY protein levels were significantly reduced (Fig. 2), to a similar degree as we observed in vitro and as has been reported for type 2 diabetic human islets (15). Together, these data validate our in vitro culture system and demonstrate the physiological relevance of our observations.…”
Section: Expression Of Acly In Beta Cellssupporting
confidence: 89%
“…ACLY is also expressed and active in pancreatic beta cells (14). ACLY levels and activity are significantly reduced in pancreatic islets from patients with type 2 diabetes (15). Several groups have investigated the role of ACLY in glucose-stimulated insulin release and have obtained conflicting results (16,17).…”
mentioning
confidence: 99%
“…We have shown that islet PPAR␥ and its target genes are hyperexpressed in nondiabetic insulin-resistant rats (present study and Refs. 6,8) and rats during the ␤-cell adaptation after a partial pancreatectomy (4, 6), plus we and others have shown impaired expression of these same genes in diabetic animals (6,29,44) and humans with type 2 diabetes (30,45,46). Collectively, these findings support, but do not prove, a FoxO1/PPAR␥-mediated transcriptional network functioning as a core element of how ␤-cells adapt to metabolic stress, with failure of this response causing or exacerbating diabetes.…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellsmentioning
confidence: 63%
“…This finding is not unique to the Px ZF model, as nuclear FoxO1 and reduced overall islet FoxO1 expression were found in insulin-resistant diabetic mice created by deletion of insulin receptors in GLUT4-expressing tissues (43). Also, below normal islet expression of Pdx1, GIP receptor, and PC is well known to occur in animals (6,28,29,44) and humans (30,45,46) with type 2 diabetes. Based on this collective evidence, we propose that nuclear retention of FoxO1 impairing PPAR␥-mediated defenses against metabolic stresses is an unrecognized feature of failed ␤-cell adaptation.…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellsmentioning
confidence: 90%
“…Recently, a report that incomplete fatty acid oxidation through depletion of TCA cycle intermediates contributed to FFAinduced insulin resistance suggest that mitochondrial dysfunction, rather than activation of lipid-mediated signals, may be a direct mediator for FFA-induced toxicity to beta cells [31]. Furthermore, decrease of various mitochondrial enzymes such as pyruvate carboxylase, glutamate dehydrogenase, isocitrate dehydrogenase, and ATP synthase in beta cells under hyperglycemic and hyperlipidemic conditions supports that mitochondrial dysfunction through metabolic failure may be a critical contributor to high glucose/FFAinduced cytotoxicity to beta cells [23,32,33].…”
Section: Introductionmentioning
confidence: 97%